High‐risk human papillomavirus infection in HIV‐positive African women living in Europe. Issue 1 (14th February 2013) - Konopnicki, Deborah; Manigart, Yannick; Gilles, Christine; Barlow, Patricia; de Marchin, Jérome; Feoli, Francesco; Larsimont, Denis; Delforge, Marc; De Wit, Stéphane; Clumeck, Nathan
Abstract : Introduction: Cervical infection with high‐risk human papillomavirus (HRHPV) induces cervical cancer and is present in 14% of women in Europe. We assessed the prevalence and incidence of cervical HRHPV in a cohort of HIV‐positive women living in Belgium. Methods: Prospective observational program of screening and follow up of HRHPV cervical infection performed by Hybrid Capture in 825 HIV‐positive women between 2002 and 2011. Women without normal cervix at baseline were excluded. Results: The final analysis included 652 women: median age 38 years, African origin (81%), median HIV follow‐up (66 months), median CD4 count (426 cells/μL) and 79% on antiretroviral therapy (cART). At baseline, HRHPV prevalence was 43% and decreased significantly as both age and CD4 cell count increased: highest prevalence (100%) in women <30 years and <200 CD4/μL and lowest (19%) in women >40 years and >500 CD4/μL (p<0.0001, multivariate analysis). The relative risk (RR) to carry HRHPV at baseline decreases proportionally by 11% for each 5 years‐age increase and by 11% for each 100 CD4 cells/μL rise (RR=0.89, 95% CI: 0.85‐0.93; p<0.0001, Poisson regression for both). During follow‐up, incidence rate of HRHPV was 13.4 per 100 women‐years. Conclusions: We found a high HRHPV prevalence of 43% and an incidence rate of 13 per 100 women‐years in this cohort of HIV‐positive women living in Europe and on cART. Women under 40 years‐age had the highest prevalence even with CD4 count >350 cells/μL. The magnitude of HRHPV epidemiology should prompt to evaluate the clinical efficacy of vaccines against HPV in HIV‐infected women.